Evaluation of the anti-arthritic activity of Cinnamomum cassia bark extract in experimental models - Himanshu Sharma; Prerna Chauhan; Surender Singh (Integrative Medicine Research, 2018)
Background: Cinnamomum cassia iswidely used as a traditional medicinal plant for the treatment of rheumatoid arthritis. Objective: The present study aimed to assess the anti-arthritic activity of C. cassia bark hydroalcoholic extract (CCHE) in different arthritic animal models. Methods: In formaldehyde model, sub-plantar administration of 0.1 ml of formaldehyde (2% v/v) into the right hind paws of Wistar albino rats on days 0 and 3. The rats were divided into six groups as follows: normal control, disease control, indomethacin group (3 mg/kg, p.o.) and three groups, treated with 50, 100 and 200 mg/kg CCHE (p.o.). Joint diameter was measured, and ankle joints were collected for MDA and GSH measurements. In complete Freund's adjuvant (CFA)-induced arthritis model, CFA was injected into the sub-plantar surface of the right hind paw in rats. Joint diameter was measured, and serum TNF-α and IL-1β were measured. Histopathological and immunohistochemical analyses were also performed. Results: CCHE treatment significantly (p < 0.01) reduced MDA levels and joint swelling in a concentration-dependent manner in rats with formaldehyde-induced arthritis, in which GSH levels were elevated (p < 0.01). In rats with CFA-induced arthritis, CCHE treatment significantly reduced joint swelling as well as IL-1β and TNF-α levels (p < 0.01). TNF-α receptor expression was decreased in rats treated with indomethacin or CCHE. Conclusion: Based on these findings, it can be concluded that C. cassia possesses anti-arthritic properties. Keywords: Arthritis, Cinnamomum cassia, Complete Freund's adjuvant, Indomethacin, Formaldehyde